LOCAL KNOWLEDGE MASYARAKAT MADURA: Sebuah Strategi Pemanfaatan Ekologi Tegal Di Madura - Moh. Hefni (Institut Agama Islam Negeri Madura)
AbstracFor Indonesia, as an agro-country, soil remains the important factor of production that can take its people to prosperity. This has been determined by the ecological structure of a certain region as well. The later factor contributes the enrichment of agriculture production level. Unlike Java island that is dominated by sawah (watery field) farming system, Madura island is covered mostly by tegalan (dry filed). Having such kind of field, Madurese do a series of research and investigation. The result is that they are able to obtain a local knowledge. This is about how to manage local natural resources that sets up an cherished and equal relationship between environment and those people. It can avoid a massive exploitation. Local knowledge is a form of environment wisdom that has been traditionally maintained and inherited from generation to generation. In running the nature, Madurese cultivates a number of plant varieties. They include subsystem plants—rice and corn, and commercial plant such as tobacco. However, not all rice varieties can be planted in tegalan. Madurese hold safety-first principle meaning they plants a certain rice variety just to complete the family needsKata-kata kuncilocal knowledge, ekologi tegal, pembuatan keputusan, jagung, padi, tembakau, subsistensi